RESERVES GROWTH AND WAYS TO IMPROVE PRODUCTIVITY - A. Kostylev; Y. Kulikova; T. Cheremisina (Вестник Северо-Кавказского федерального университета, 2022)
One of the main tasks of a progressive economy is to increase productivity. Its level is largely guided by the pace offinancial recovery, the availability of goods and proposals, the competitiveness of the economy, the welfare of society. Increasing labor productivity is a key task of the Russian economy at the present stage. In recent years, the level of labor productivity in Russia lags far behind the same indicator in foreign countries. In this article the factors influencing labor productivity in Russia are considered, ways of its increase are planned.